The Course of Industrial Decline: The Boott Cotton Mills of Lowell, Massachusetts, 1935-1955 - Tone, Andrea Kluge (Labour / Le Travail, 1995)
The article reviews the book, "The Course of Industrial Decline: The Boott Cotton Mills of Lowell, Massachusetts, 1935-1955," by Lawrence Gross.
Keywords: BOOKS – Reviews; BUSINESS failures; COURSE of Industrial Decline: The Boott Cotton Mills of Lowell; Massachusetts 1835-1955; The (Book); GROSS; Lawrence; Nonfiction